Effectiveness of medium chain fatty acid (MCFA) products and their ability to replace ZnO or carbadox in weanling pig diets - Dahmer, Payton L.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
The objective of this experiment was to evaluate medium chain fatty acids (MCFA) effects on nursery pig performance in place of ZnO and carbadox. In this trial, 360 weanling pigs (DNA 200 x 400; 5.4 ± 0.07 kg BW) were fed for 35 days, with 6 pigs/pen and 10 replicate pens/treatment. Pigs were allotted in a completely randomized design to one of 6 treatment diets: 1) control; 2) 3,000 ppm ZnO during Phase 1 and 1,500 ppm ZnO in Phase 2; 3) 50g/ton carbadox; 4) 1% blend of C6:C8:C10; 5) 1% Feed Energy R2 (Feed Energy Corp, Des Moines, IA); 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). Treatment diets were fed in two phases from weaning to d 19 of the experiment, and a common Phase 3 diet was fed from d 19 to 35. From d 0 to 19, pigs being fed the ZnO or Carbadox diets showed increased (P<0.05) ADG compared to pigs being fed the control or R2 diets. Additionally, pigs being fed the C6:C8:C10 or FORMI diets had similar (P>0.05) ADG compared to those fed carbadox. Differences in ADFI throughout the treatment period (P=0.004) served as the driver behind these effects, while G:F differences were marginally significant (P=0.078). Increased d 19 BW (P<0.05) was observed for pigs fed ZnO and carbadox in relation to the negative control, while other treatments were intermediate. No significant impact was demonstrated on G:F (P=0.320). Overall, these results show that ZnO and carbadox are valuable additives to help maximize growth performance in early stages of the nursery. Some MCFA products, like FORMI GML, may result in similar performance, while others restrict performance. Thus, additional research is needed to study the effectiveness of MCFA to replace ZnO or feed-based antibiotics.
Keywords: Spring 2019